Aplikasi Pengenalan Dasar Pancasila sebagai Inovasi Pembelajaran Digital Berbasis Android - Shandy Juniantoro; Munich Heindari Ekasari; Neneng Mariana (CV. ITTC INDONESIA, 2026)
This research focuses on developing an Android-based learning application that introduces the fundamental principles of Pancasila. The main problem addressed is how to design a learning medium that is interactive, accessible, and suitable for students in understanding Pancasila’s core values. Traditional learning methods are often less engaging, which can reduce students’ interest in civic education. Therefore, a technology-based solution is needed to improve both comprehension and motivation. The purpose of this study is to produce an Android-based application that can be used as an educational tool to introduce Pancasila values to students. This application is expected to help students better understand the material and also assist teachers as a supporting medium in classroom learning. By combining interactive features, clear content, and an appealing interface, the application aims to create a more engaging learning experience. This research applies the Research and Development (R&D) method, focusing on the validation and effectiveness of learning materials, along with the Software Development Life Cycle (SDLC) using the waterfall model to ensure proper technical development. Based on testing results, the application functions well from both developer and user perspectives. It is expected to enhance students’ understanding of Pancasila and increase their enthusiasm for learning while fostering a sense of citizenship.